Shock index and TIMI risk index as valuable prognostic tools in patients with acute coronary syndrome complicated by cardiogenic shock. - Karolina Supeł; Michał Kacprzak; Marzenna Zielińska (PLoS ONE)
Background The aim of the study was to evaluate the usefulness of the shock index (SI) and the TIMI risk index (TRI Thrombolysis in Myocardial Infarction Risk Index) one hour after successful primary percutaneous coronary intervention (pPCI) for predicting in-hospital mortality in patients with acute coronary syndrome complicated by cardiogenic shock (CS). Methods Forty-seven consecutive patients with acute myocardial infarction (AMI) complicated by CS were included in this prospective observational study. All patients underwent pPCI and obtained TIMI Grade Flow 3. SI and TRI were calculated one hour after pPCI. Results The primary endpoint-death from cardiovascular causes-occurred in 17 patients (36%). All calculated parameters were significantly higher in fatal CS than in the non-fatal CS group. A multivariate logistic regression model found only TRI to be an independent, significant predictor of death in the study group, with a proposed cut-off point of 66, with sensitivity 76.5% and specificity 83.3% (AUC 0.811, p = 0.00001). Conclusions The simple parameters of clinical assessment-SI and TRI-calculated one hour after a successful pPCI of infarct related artery are important predictors of death in AMI complicated by cardiogenic shock.